Potential of the Burkholderia cepacia Complex to Produce 4-Hydroxy-3-Methyl-2-Alkyquinolines - Coulon, Pauline M. L.; Groleau, Marie-Christine; Déziel, Eric (Frontiers in Cellular and Infection Microbiology, 2019)
A few Burkholderia species, especially Burkholderia pseudomallei, Burkholderia thailandensis, Burkholderia ambifaria and Burkholderia cepacia, are known to produce and release various 4-hydroxy-3-methyl-2-alkylquinolines (HMAQs), a family of molecules analogous to the 4-hydroxy-2-alkylquinolines (aka 2-n-alkyl-4(1H)-quinolones) of Pseudomonas aeruginosa, which include the Pseudomonas quinolone signal (PQS). However, while these exoproducts play several roles in P. aeruginosa virulence and survival, the available literature is very limited on their distribution and function in Burkholderia. Here, we studied the distribution of the hmqABCDEFG operon, which encodes the enzymes involved in the biosynthesis of HMAQ, in the Burkholderia cepacia complex (Bcc) group. Based on the available sequence data, about one third of Bcc species carry a homolog of the hmqABCDEFG, and not all sequenced strains in a given species possess this operon. Looking at the synteny of genes surrounding the hmqABCDEFG operon, we found that for some species, the operon seems to have been deleted or replaced by other genes. Finally, we review the literature on the possible function of HMAQs. Understanding the Hmq system may provide clues concerning their functions in Bcc